Maximum Phonation Time of School-Aged Children in Pakistan: A Normative Study : Maximum Phonation Time of School-Aged Children - Naeem, Iqra; Mubeen, Raffa; Shah, Syed Aftab Haider; Obaid, Sumaiyah; Saqulain, Ghulam (Pakistan Journal of Health Sciences, 2024)
Maximum phonation time (MPT) evaluates maximum vocal capabilities and can be used to assess the effectiveness of behavioral and medical therapy interventions. There is a literature gap regarding MPT normalcy data for Pakistani children. Objective: To determine the Maximum Phonation Time of School Aged Children in Pakistan and its association with participant variables and impact of the 6-minute walk test on participant vitals. Methods: This cross-sectional survey was conducted in Rawalpindi and Islamabad on typical healthy school-aged children from August 2021 to January 2022. The sample included both genders, aged 6-13 years having normal language. Tools used included a basic demographic sheet, token test, stopwatch, growth chart, sphygmomanometer, pulse oximeter, and 6-minute walk test. Blood Pressure, oxygen saturation, heart rate, and MPT were calculated before and after the six-minute walk test (6-MWT). Data were analyzed by using SPSS version 21.0. Results: Results show MPT of 13.11 ± 3.93 seconds. Scores were significantly (p= 0.000) higher for higher age groups. 6-MWT revealed a significantly (p=0.000) higher post walk SPO2 (99.16 ± 0.89 Vs.97.82 ± 1.45), HR (105.94 ± 14.53 vs 92.94 ± 14.79). systolic (112.46±13.40 vs. 107.25 ± 13.66) and diastolic blood pressure (79.07 ± 8.17 Vs.73.84 ± 8.50) compared to pre walk. A significantly (p<0.001) strong positive correlation was noted for age(r=.515), weight (r=.460), height (r=.491) and distance (r=.281). Conclusions: MPT of Pakistani 6-13 years children is 13.11 ± 3.93 seconds with significantly higher MPT for higher age groups. MPT has a strong positive correlation with age, weight, height and distance and increases after walking. MPT values for boys were slightly higher than for girls.